Representação documentária das plantas arquitetônicas do projeto CAT (Centro Agroambiental do Tocantins) - SILVA, Tayza Stefanie Marçal (2018)
The objective of this research is to discuss the representation of the information of the architectural plants of the Tocantins Agro-environmental Center, explain about indexing concepts and cartographic material, analyze and demonstrate its importance for the field of research. The exploratory research methodology was used to approach concepts, classification and informational relevance of cartographic materials in the area of librarianship in the main data bases of the area, and carrying out a case study in the technical treatment and representative analysis of the information in the 23 architectural plans of the CAT project and its historical context. Therefore the importance of the technical treatment of this type of non-conventional material to librarians, but of great importance for it to be harnessed and disseminated to the affine public.